IMPLEMENTATION OF HEALTH SERVICE STRATEGY AT KUTALIMBARU HEALTH CENTER MEDAN TUNTUNGAN - Rahayu, Sri; Hannari, Marysha Ikhmaniar; Syaharani, Latifah; Syahfitri, Dewi; Nst, Rabitha Khailila Ihrom; Karera, Anggi Indah; Salsabila, Rizka fauziah; Pulungan, Dea Rizka Ananda; Adelia, Difa; Wasiyem, Wasiyem (HEARTY, 2025)
The health center as a first-level health service center has a strategic role in improving the health of the community in its working area. The implementation of service strategies at the Kutalimbaru Health Center, Medan Tuntungan also faces challenges such as limited human resources, facilities, and suboptimal community responses. Method: using a qualitative approach with a descriptive design. This study was conducted through primary and secondary data collection which included in-depth interviews with key informants, namely the head of the health center and the person in charge of health management services. The study was conducted at the Kutalimbaru Health Center, Medan Tuntungan on Thursday, April 23, 2025. Objective: The purpose of this study was to obtain an up-to-date picture of the implementation of health service strategies at the health center. The focus of the study was the effectiveness of the service strategies implemented and the obstacles faced in efforts to improve the quality of health services to the local community. Results: The results of this study are that the implementation of health service strategies at the Kutalimbaru Health Center was carried out by holding Mobile Health Centers and Village Health Posts as an effort to expand access to health services to the community, especially in hard-to-reach areas. Conclusion: The results of this study highlight that Partnership and Community Empowerment Strategies are the main keys to improving access and quality of health services. Through close cooperation between the Health Center, Integrated Health Posts, village governments, and various related parties, maternal, adolescent, and toddler health programs can run effectively, thereby reducing the risk of stunting, anemia, and increasing immunization coverage.